Optical trapping and optical force positioning of two-dimensional materials. Issue 3 (2nd January 2018) - Donato, M. G.; Messina, E.; Foti, A.; Smart, T. J.; Jones, P. H.; Iatì, M. A.; Saija, R.; Gucciardi, P. G.; Maragò, O. M.
Abstract : Optical forces are used for trapping, characterization, and positioning of layered materials (hBN, MoS2, and WS2 ) obtained by liquid phase exfoliation. Abstract : In recent years, considerable effort has been devoted to the synthesis and characterization of two-dimensional materials. Liquid phase exfoliation (LPE) represents a simple, large-scale method to exfoliate layered materials down to mono- and few-layer flakes. In this context, the contactless trapping, characterization, and manipulation of individual nanosheets hold perspectives for increased accuracy in flake metrology and the assembly of novel functional materials. Here, we use optical forces for high-resolution structural characterization and precise mechanical positioning of nanosheets of hexagonal boron nitride, molybdenum disulfide, and tungsten disulfide obtained by LPE. Weakly optically absorbing nanosheets of boron nitride are trapped in optical tweezers. The analysis of the thermal fluctuations allows a direct measurement of optical forces and the mean flake size in a liquid environment. Measured optical trapping constants are compared with T-matrix light scattering calculations to show a quadratic size scaling for small size, as expected for a bidimensional system. In contrast, strongly absorbing nanosheets of molybdenum disulfide and tungsten disulfide are not stably trapped due to the dominance of radiation pressure over the optical trapping force. Thus, optical forces are used to pattern a substrate by selectively depositing nanosheets in short times (minutes) and without any preparation of the surface. This study will be useful for improving ink-jet printing and for a better engineering of optoelectronic devices based on two-dimensional materials.